2011
DOI: 10.4038/cmj.v56i2.3112
|View full text |Cite
|
Sign up to set email alerts
|

Uses of a familial adenomatous polyposis registry

Abstract: Objectives To improve the prognosis of patients with familial adenomatous polyposis (FAP) by early diagnosis and prophylactic treatment through a coordinated FAP register.Design The establishment and descriptive analysis of the prospective database of the FAP registry.Setting University surgical unit, Colombo North Teaching Hospital Ragama, Sri Lanka.Patients Probands were identified by tracing all diagnosed FAP patients from 1996 to 2010 and their family members at risk.Interventions The establishment of a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Overall 109 children were identified with hepatoblastoma and FAP, regardless of whether or not genetic testing was performed (Table , Supplementary Table S1) . Of 90 patients with gender data reported, 65 were males (2.6:1 male:female).…”
Section: Resultsmentioning
confidence: 99%
“…Overall 109 children were identified with hepatoblastoma and FAP, regardless of whether or not genetic testing was performed (Table , Supplementary Table S1) . Of 90 patients with gender data reported, 65 were males (2.6:1 male:female).…”
Section: Resultsmentioning
confidence: 99%
“…Data from an Australian hospital‐based FAP registry showed a reduction in CRC incidence from 75 to 6 per cent with screening, and a study from Hong Kong demonstrated a reduction from 61 to 10 per cent. Smaller studies from Singapore and Sri Lanka have shown similar trends, although methodological quality was poorer.…”
Section: Resultsmentioning
confidence: 95%
“…Thirty studies compared CRC incidence and/or mortality in screened and symptomatic groups in FAP including 8016 individuals ( Table S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Collaborative Group of the Americas on Inherited Colorectal Cancer was established in 1995 and developed registries for patients with inherited colorectal cancer disorders, including FAP, at 14 cancer centers in the United States and Canada that help in selection of appropriate screening tests/therapy and managing the multidisciplinary care of the disorder. Studies have shown that FAP patients enrolled in registries for inherited colorectal cancer have improved outcomes compared to those treated in centers without such registries and can improve the prognosis of FAP due to earlier detection . Therefore, we argue that patients enrolled in FAP registries have better access to screening TUS than that at institutions without registries.…”
Section: Discussionmentioning
confidence: 93%